Analytical and experimental determination of the failure-critical pressure of pipe structures manufactured by PBF-LB/M - Koers, Thorsten; Magyar, Balázs; Bödger, Christian; Tröster, Thomas (International Journal of Pressure Vessels and Piping)
The state of the art shows that PBF-LB/M offers great potential for pressure-loaded parts, with significant weight reductions and simultaneous optimization of flow resistance. This study is aimed at applying existing calculation methods for pressure-loaded parts to additively manufactured pipe structures, considering the two materials EN AC-43000 (3.2381, AlSi10Mg) and AISI 316L (1.4404, X2CrNiMo17-12-2). For this purpose, systematic tensile tests are carried out for both materials. In addition, a statistical evaluation is performed to determine the design-relevant strength characteristics with a survival probability Ps of 97.5 % for both materials in the as-built and heat-treated condition. Pipe specimens are manufactured, half of which are heat treated, geometrically measured and then subjected to a burst pressure test to experimentally determine the failure-critical internal pressure. These results are compared with calculated burst pressures. The calculations are based on the application-relevant methods identified in this study, considering the strength values determined for the respective material condition. This comparison is used to assess the suitability of the calculation methods for additively manufactured pipe structures, based on the materials investigated.
Keywords: PBF-LB/M; Pipe structures; Strength assessment; Burst pressure test; Geometrical deviations

Compensation of the Shrinkage Behavior Occurring in Cylindrical Components in the FDM Process - Koers, Thorsten; Magyar, Balázs (Macromolecular Symposia)
Fused deposition modeling (FDM) is an additive manufacturing process that can be used to manufacture three-dimensional thermoplastic components layer by layer. One disadvantage of FDM is the shrinkage of the components during the manufacturing process. The filament is molten in the nozzle, deposited layer by layer, and cools down again. During solidification, the filament shrinks inhomogeneously in the x/y/z direction, which leads to distortion of the component geometries. Particularly with higher nominal lengths and complex local geometries, there is a need for optimization with regard to dimensional accuracy. The aim of this paper is to counteract this on the software side with global as well as local shrinkage factors. The expected shrinkage within a layer is predicted with an in-house developed software. The geometric accuracy of the model is verified by experimental investigations on cylindrical test specimens. In these, the so-called clover effect occurs as a result of the shrinkage. The circular shape of the deposited layer is deformed by the distortion in the x–y plane comparable to a clover. Finally, the results are validated by analyzing a demonstrator in the form of a bracket.

Determination and Compensation of the Shrinkage Behavior of Cylindrical Elements in the FDM Process - Koers, Thorsten; Magyar, Balázs (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
Fused Deposition Modeling (FDM) is an additive manufacturing process to produce complex thermoplastic geometries layer by layer. The filament is melted in a nozzle, iteratively deposited, and then cools down. Due to the solidification process, the deposited filament strands deviate from their intended position due to shrinkage, resulting in significant geometric deviations in the final part. In terms of dimensional accuracy, there is a need for optimization, especially for local curved geometries in relation to the global part with higher nominal dimensions. The aim of this study is to investigate the size and shape deviations for cylindrical FDM elements and to compensate the expected deformations by using an in-house software with adaptive scaling factors in the x-y plane. Previous studies mainly focus on simple, non-curved objects, this study also considers the influence of curvature and global as well as local deviations on the final part.

Depiction of support structures in technical drawings - Lammers, Stefan; Koers, Thorsten; Magyar, Balázs; Zimmer, Detmar; Lieneke, Tobias (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
To ensure uniform documentation of support structure information, a concept is presented that enables a standardized depiction of support structures in technical drawings based on ISO 128-3. To this end, requirements for a uniform depiction are defined and a procedure for drawing entry is presented. The drawing entry should contain all production-relevant support structure information. The standardized documentation of support structure information in technical drawings is intended to ensure a simple, clear and safe exchange of information between business units or different companies along the value chain. As a result a possible drawing entry of support structures was developed. To distinguish between different support structure types, a standardized depiction of geometrical information in a specification field is shown. The specification field gives a detailed description of the support structure type, the geometry as well as the connection to the part and the building platform. Also uncommon support types like lattice structures or CAD based support structures can be implemented. To ensure the usability the depictio is editable and extendable.

Zukunftstechnologie und moderne Antriebe kombiniert: AM in modularen Antriebssystemen - Zimmer, Detmar; Koers, Thorsten; Bührmann, Tobias (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)